Endoscopic ultrasound and endoscopic ultrasound-guided fine needle aspiration in the diagnosis of diffuse gastrointestinal lesions with inconclusive endoscopic biopsies - Okasha, Hussein Hassan; Elkholy, Shaimaa; Sayed, Mohamed; Mahdy, Reem Ezzat; ElSherif, Yehia; El-Gemeie, Emad; El-Magd, Amr Abo (Turkish Journal of Gastroenterology, 2017)
Abstract Background/Aims: Many gastrointestinal tumors appearing as diffuse circumferential malignancies, for example, diffuse signet ring adenocarcinoma and lymphoma, might primarily involve the submucosal layer and hence are difficult to diagnose because they frequently yield negative endoscopic biopsies. This main aim of this study was to evaluate the accuracy of endoscopic ultrasound (EUS) and EUS-guided fine-needle aspiration (EUS-FNA) in the diagnosis of diffuse gastrointestinal lesions with inconclusive endoscopic biopsies. Materials and Methods: This prospective study included 92 patients with diffuse or circumferential gastrointestinal lesions with non-conclusive biopsies that were taken during upper or lower endoscopy. EUS and EUS-FNA were performed on all patients with cytopathological examination. Results: This study included 58 males (63%) and 34 females (37%) with a mean age of 54.2 years. Seventy-two cases (78.3%) were shown to have malignant lesions, and 20 cases (21.7%) were shown to be benign. EUS had a sensitivity of 94.4%, a specificity of 65%, a positive predictive value (PPV) of 90.7%, and a negative predictive value (NPV) of 45.1% with a p Conclusion: Endoscopic ultrasound with EUS-FNA is an accurate procedure in the diagnosis of endoscopic biopsy-negative diffuse or circumferential gastrointestinal lesions. Cite this article as: Okasha HH, Elkholy S, Sayed M, et al. Endoscopic ultrasound and endoscopic ultrasound-guided fine needle aspiration in the diagnosis of diffuse gastrointestinal lesions with inconclusive endoscopic biopsies. Turk J Gastroenterol 2017; 28: 370-6